the impact of the strategy of ideas gardens in the Achievement of fifth grade students in Science and the development of their curiosity. (Journal of the College of Basic Education, 2022)
the impact of the strategy of ideas gardens in the Achievement of fifth grade students in Science and the development of their curiosity., . The research was represented by The sample that included (44) students of the( Samarra) primary school as ( 22) students for the experimental group, studied by the Gardens of Ideas strategy ,and (22) students for the control. group depending on the normal method., the test consisted of (30) items as multi-choice type, and the reliability was (0.85). The development of curiosity has prepared to and it consisted (20) items . The results of the research indicated that the experimental group outperformed the control group in achievement and curiosity. The research suggest the need to adopting new teaching strategies.